Granzyme-b is involved in mediating post-ischemic neuronal death during focal cerebral ischemia in rat model - Ganta, Vijay; Schwaninger, Markus; Alexander, J. S.; Babu, P. Prakash (Neuroscience, 2010)
Although peripheral immune cells infiltrate ischemic infarct tissue and elicit immune injury, the role of Cytotoxic T Lymphocytes (CTLs) and the toxins they release in mediating neuronal death is not well understood. Granzyme-b (Gra-b), a serine protease found in the cytoplasmic granules of CTLs and natural killer cells, plays an important role in inducing target cell death by activating several caspases and by initiating caspase-independent pathways that contribute to target cell death. To determine if CTLs and Gra-b are involved in post-ischemic cerebral cell death; we investigated the role of CD8(+) CTLs and Gra-b in ischemic rat brain infarct after transient middle cerebral artery occlusion (tMCAO) and in sham-operated animals. We observed that CTLs infiltrate the ischemic infarct within 1 h of reperfusion. There was a significant increase in Gra-b levels in the ischemic region starting from 1 h until 3 day which correlated with increased levels of chemokines (IP-10/CXCL10, IL-2) and TNF-alpha. Co-immunoprecipitation experiments show that Gra-b interacts with Bid, PARP, and caspase-3 in ischemic samples. Immunofluorescence analysis of Gra-b and TUNEL showed that Gra-b is present both in apoptotic and necrotic cells. Triple immunostaining further confirmed that the Gra-b positive degenerating cells were neurons. CTLs in close spatial proximity to degenerating neurons, increased levels of Gra-b, localization in neurons positive for TUNEL, and interaction with other pro-apoptotic proteins indicate that Gra-b and CTLs play a significant role in neuronal death following cerebral ischemia in the rat brain after tMCAO. Based on the above findings we support our hypothesis that Gra-b secreted from activated CTLs might be involved in aggravating post-ischemic damage by mediating neuronal death.
Available online 4 November 2009
Gesehen am 31.01.2023